2009
DOI: 10.2334/josnusd.51.301
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome: a case report

Abstract: Cranio-dento-facial findings in a case of Noonan syndrome in a 13-year, 3-month-old male are reported. Oral examination of the patient revealed a narrow, high arched palate, malocclusion and congenitally missing teeth. Even though cephalometric measurements showed an increased vertical facial pattern (GoGn/SN = 38.46 degrees ), a severe deep bite (9 mm) was evident. Noonan syndrome is characterized by ocular, facial, cardiac, and dental anomalies, although it is often unrecognized by clinicians. Although diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
0
25
2
Order By: Relevance
“…Hereditary is believed to be an important etiological factor in the occurrence of supernumerary teeth. 16 Although there are many cases of children with NS and dental abnormalities reported, 8,11,12,17,18 there were only two previous cases with supernumerary teeth reported in the childhood. 17,18 Mutation analysis of these cases with supernumerary teeth were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hereditary is believed to be an important etiological factor in the occurrence of supernumerary teeth. 16 Although there are many cases of children with NS and dental abnormalities reported, 8,11,12,17,18 there were only two previous cases with supernumerary teeth reported in the childhood. 17,18 Mutation analysis of these cases with supernumerary teeth were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that periodontal problems may occur in patients with NS due to a lack of space in the jaw. 12,17 Gingivitis was noted in present case, therefore oral hygiene education has been given and gum treatment applied to the patient. Orthodontic treatment was planned for the patient for the lack of space in the jaw.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The primary features of this multisystem disorder include hypertelorism, low-set ears, downslanting eyes, a webbed neck, congenital heart diseases, short stature, chest deformity, and intellectual impairment. 2,3 NS affects males and females equally and has an estimated incidence of 1 in 1000 to 1 in 2500 live births. 2,4 The challenges faced during anesthetic management of patients with NS could be due to congenital heart diseases, hemostatic disorders, and airway anomalies.…”
mentioning
confidence: 99%